Aplicações diagnósticas da termografia infravermelha em canídeos e felídeos selvagens ex-situ - Costa, André Luiz Mota da (Universidade Federal de São Carlos, 2018)
Infrared thermography is a noninvasive diagnostic imaging method that does not require animal restraint. This tool provides instant images, in real time, even at great distances, being very advantageous for wild animals. The thermograph, which measures the frequency of infrared rays, locates hot or cold regions in the body tissues, detecting physiological or pathological processes that modify body temperature. Compared with other imaging modalities, it does not require anesthesia, and does not expose the patient to radiation. In the veterinary diagnosis of wild animals, thermal imaging is used to determine causes of lameness, lesions and inflammation; in the diagnosis of infectious diseases, reproductive period and gestation; and to assess animal welfare and stress levels. This research aimed to use infrared thermography as a tool for remote diagnosis in wild canids and felids kept ex-situ. The research was developed at the Municipal Zoo "Quinzinho de Barros" in Sorocaba, state of São Paulo. During one year the images were recorded biweekly in 45 individuals, 18 of the Canidae Family and 27 of the Felidae Family. The device used to capture the images was the FLIR T460 thermograph. During the study no thermal change was noticed in the images taken biweekly. Twelve animals presented symptoms at different times, and images were taken immediately and then recorded every 3 days to follow the evolution of the clinical signs and treatment. Thermal alterations of the images were interpreted and correlated with the clinical signs. The method showed good sensitivity when applied to felids, as they present short hair, allowing a better capture of the heat emitted by the local tissues. In the canids there was good sensitivity for head and limb disorders, because these regions have shorter hair. It is concluded that thermography is a good diagnostic tool for canids and felids, assisting in diagnosis or guiding the veterinarian in their conduct; being an examination carried out at a distance, without stress, non-invasive and painless, prioritizing animal welfare.
Diagnostic applications of infrared thermography in ex-situ wild canids and felids
Keywords: Zoológico; Imaginologia; Carnívoros; Bem-estar Animal; Zoo; Imaging; Carnivores; Animal Welfare; CIENCIAS AGRARIAS::MEDICINA VETERINARIA::CLINICA E CIRURGIA ANIMAL